ON Ia- CONNECTED SPACES VIA IDEAL - Hassan, Hanan Zaky; Radwan, A. E; Elgawad, A. A. Abd; Mahmoud, Safaa (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
The aim of this paper is to study some properties of - open set in ideal topological spaces, which was introduced by M.E. Abd El-Monsef [1], such as interior, exterior, functions and connectedness.